Some Empirical Aspects of Entrepreneurship - Evans, David S.; Leighton, Linda S. (American Economic Review, 1989)
About 4.2 million men and women operate businesses on a full-time basis. Comprising more than a tenth of all workers, they run most of our nation’s firms and employ about a tenth of all wage workers. The fraction of the labor force that is self-employed has increased since the mid-1970s after a long period of decline.1 This paper examines the process of selection into self-employment over the life cycle and the determinants of self-employment earnings using data from the National Longitudinal Survey of Young Men (NLS) for 1966–1981 and the Current Population Surveys for 1968–1987.